Potential Influence of the Microbiome on Infertility and Assisted Reproductive Technology - Sirota, Ido; Zarek, Shvetha M.; Segars, James H. (Seminars in Reproductive Medicine, 2014)
Although an altered vaginal microbiota has been demonstrated to affect parturition, its role in assisted reproductive technologies is uncertain. Nevertheless, the effect of known pathogens such as Mycoplasma tuberculosis, Chlamydia trachomatis, and Neisseria gonorrhoeae is clear, causing subclinical changes thought to be risk factors in subfertility. The Human Microbiome Project (HMP) has allowed for metagenomic studies to aid in characterizing normal vaginal flora. Recent findings from the HMP demonstrate that many different species of Lactobacillus are present in the vaginal tract, with a few that predominate. Studies that characterize the vaginal microbiome in assisted reproductive technology support the hypothesis that colonizing the transfer-catheter tip with Lactobacillus crispatus at the time of embryo transfer may increase the rates of implantation and live birth rate while decreasing the rate of infection. In addition, there is some evidence that a progesterone-resistant endometrium might increase the risk of an abnormal vaginal microbiome.
Keywords: microbiome; in vitro fertilization; Lactobacillus; progesterone